Patient Experience and Attitudes Toward Addressing the Cost of Breast Cancer Care. (1st October 2014) - Irwin, Blair; Kimmick, Gretchen; Altomare, Ivy; Marcom, P. Kelly; Houck, Kevin; Zafar, S. Yousuf; Peppercorn, Jeffrey
Abstract : Background: The American Society of Clinical Oncology views patient‐physician discussion of costs as a component of high‐quality care. Few data exist on patients' views regarding how cost should be addressed in the clinic. Methods: We distributed a self‐administered, anonymous, paper survey to consecutive patients with breast cancer presenting for a routine visit within 5 years of diagnosis at an academic cancer center. Survey questions addressed experience and preferences concerning discussions of cost and views on cost control. Results are primarily descriptive, with comparison among participants on the basis of disease stage, using chi‐square and Fisher's exact tests. All p values are two‐sided. Results: We surveyed 134 participants (response rate 86%). Median age was 61 years, and 28% had stage IV disease. Although 44% of participants reported at least a moderate level of financial distress, only 14% discussed costs with their doctor; 94% agreed doctors should talk to patients about costs of care. Regarding the impact of costs on decision making, 53% felt doctors should consider direct costs to the patient, but only 38% felt doctors should consider costs to society. Moreover, 88% reported concern about costs of care, but there was no consensus on how to control costs. Conclusion: Most breast cancer patients want to discuss costs of care, but there is little consensus on the desired content or goal of these discussions. Further research is needed to define the role of cost discussions at the bedside and how they will contribute to the goal of high‐quality and sustainable cancer care. Abstract : Most breast cancer patients want to discuss costs of care, but there is little consensus on the desired content or goal of these discussions. A self‐administered, anonymous survey was given to breast cancer patients presenting for a routine visit within 5 years of diagnosis at an academic cancer center. Survey questions addressed experience and preferences concerning discussions of cost and views on cost control. Results are primarily descriptive.